Information Frictions and Labor Market Outcomes - Ana Rute Cardoso; Annalisa Loviglio; Lavinia Piemontese (Institute for the Study of Labor (IZA), 2015)
We analyze the impact of information frictions on workers' wages, contributing to the literature that tested search theory, which has so far focused on labor market frictions in general and not specifically on information asymmetries. Using data for 16 countries from the European Social Survey 2008, we find a sizeable gap between workers' perceptions of the unemployment rate and the actual unemployment rate in the country, which is a meaningful indicator of their misperception of labor market tightness. To handle the interval nature of our outcome of interest, the earnings variable, we estimate interval regressions, as well as ordered probit models. We follow a threefold strategy to tackle potential endogeneity problems, as the model includes: controls for the worker's ability; country-specific fixed effects; the unemployment rate in the region of residence, which might be the benchmark respondents have in mind when reporting their perception of the national unemployment rate and which is known to influence regional wages. Results show that when subjective perceptions overstate the unemployment rate in the country, a one percentage point gap between the perceived and the actual unemployment rate reduces individual wages by 0.4 to 0.7 percent. We discuss a potential mechanism generating this result. A pessimistic view of the labor market leads to concern over own future employment prospects and is thus likely to lower reservation wages; a too optimistic view, in turn, could raise reservation wages, but it would render job finding more difficult.
Keywords: J31; J42; J64; 330; job search; matching; unemployment; frictions; wage dispersion; labor market tightness